Azobenzene Photoswitches for Staudinger–Bertozzi Ligation1. Issue 7 (10th January 2013) - Szymański, Wiktor; Wu, Bian; Poloni, Claudia; Janssen, Dick B.; Feringa, Ben L.
<x xml:space="preserve">Abstract</x> Click to switch: A novel family of azobenzenes containing residues needed for aqueous Staudinger–Bertozzi ligation to azides was designed (see scheme). The resulting photochromes show stable and reversible switching behavior in water, with a photostationary state (PSS) of up to 95:5 cis/trans. Applications in model systems include the modification of azide‐bearing surfaces and proteins.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>